Avaliação da contaminação por desoxinivalenol em arroz e farelo de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Deoxynivalenol (DON) is a mycotoxin produced by fungi of the genus Fusarium that has high stability to heating and can remain in the product for several years. The objective of this work was to evaluate the DON content in rice samples commercialized in the region of the West Frontier of the State of Rio Grande do Sul and in samples of rice bran yielded by local companies, through High Performance Liquid Chromatography (HPLC) and visible ultraviolet detector (UV-VIS). The analytical method employed was validated following the performance parameters recommended by the ANVISA and INMETRO guides, being: selectivity, limit of detection and quantification, linearity, precision and accuracy. The mycotoxin was extracted by the solvent mixture acetonitrile:water (85:15), from which the supernatant was collected, evaporated at 60 °C, resuspended with water:acetonitrile:methanol (90:5:5) and filtered with a syringe filter. The method was selective, linear, precise, robust, with adequate quantification (230 μg.Kg-¹) and detection (69 μg.Kg-¹) limits. In this way, the proposed analytical method can be reproduced in other laboratories, including in the routine quality control of the processing industries for the determination of DON in rice and rice bran. It was possible to quantify DON contents in two samples of polished parboiled rice, one of whole rice and all of rice bran, because they presented higher quantities than the limit of quantification of the developed method. The sample of parboiled rice bran presented higher contamination by DON (754.26 μg.Kg-¹) in relation to the other samples. However, all the samples evaluated had levels of DON in compliance with the maximum limits tolerated by Brazilian legislation for mycotoxin.
Keywords: Fungos; Fusarium; Micotoxina; Arroz parboilizado; Arroz integral; Cromatografia; Fungi; Mycotoxin; Parboiled rice; Whole rice; Chromatography; CNPQ::CIENCIAS AGRARIAS